Book Review: Museums, History and Culture in Malaysia - Ahmad, Abu Talib (Penerbit Universiti Sains Malaysia (USM Press), 2016)
It is not very often that one comes across a book about museums in Malaysia. Neither can one easily find such a book that has its contents closely intertwined with the history and culture of the country. This is because an attempt to link the museums with history and heritage is indeed full of complexities as the author has tried to show. The book nonetheless shows that such task is possible. In fact, for college students, the book is quite helpful in providing useful historical information of Malaysia's past. From the narratives of the book, readers will certainly be made aware about the truth of the saying that Malaysia is unique in every sense of the word. As a multi-cultural and multi-ethnic country, it is unique in its style of political pragmatism as seen from the unconventional way its political elites try to manage a plural society that is still struggling to become a viable and integrated nation. Through his book, Museums, History and Culture in Malaysia, the author Abu Talib Ahmad has painstakingly demonstrated how museums in Malaysia try to cope with the diverse and pluralistic views of the country's history